Helsinki Olympialaisten aikaan 1952 - Sundström, Hugo
innehållsbeskrivning: Trafik i Helsingfors i juli 1952.
Keywords: olympiska spelen; olympiska spelen; Helsingfors olympiad; trafik; städer; Suomi, Uusimaa, Helsinki